Fuzzy-Set Based Privacy Preserving Access Control Techniques in Cloud (FB-PPAC) - Sushmita Kumari; Sudha S; Brindha K (Institute of Advanced Engineering and Science, 2017)
The word “Cloud” refers to network or internet. It is present at.remote location. Cloud computing is a latest mechanism used now-a-days for accessing, manipulating and configuring applications online via internet. It allows users for online data storage, various applications and infrastructure. There are few downsides of cloud computing like in public cloud sharing of data, selected data shared with users of various level without confidentiality and privacy of data. Different methods were used to fix this problem like encryption of attribute; encryption of access control but they have their own problems related to big computation for accquiring access structure, invoking and behavior management. So for removing these weakness, the combination of fuzzy-set theory and RSA algorithm has been introduced. Fuzzy-set is used for clustering the data based on their points. Further for privacy, I have included RSA for encryption and decryption of data which is used to store in cloud database. The analysis of my experiment shows the system is efficient, flexible and provides confidentiality of the data.